Vous êtes sur la page 1sur 2

CPSC 302 2008W T1

Convergence order of the Secant method



1+ 5
In this note I will show that the secant method convergence order is 2
≈ 1.62.

The secant method reads:


f (xn )(xn − xn−1 )
xn+1 = xn − . (1)
f (xn ) − f (xn−1 )

Let us define the (signed) error ek as

ek = xk − x∗ ,

where x∗ is the exact solution, i.e., f (x∗ ) = 0. To figure out the convergence order (which
will turn out to be superlinear) we have to find a relation between en+1 and en . As in the
corresponding derivation for Newton’s method we use Taylor’s theorem to write:
1
f (xn ) = f (x∗ + (xn − x∗ )) = f (x∗ + en ) = f (x∗ ) + f 0 (x∗ )en + f 00 (x∗ )e2n + O(e3n ).
2
In Eq. 1 f (xn−1 ) also appears and we write similarly
1
f (xn−1 ) = f (x∗ +(xn−1 −x∗ )) = f (x∗ +en−1 ) = f (x∗ )+f 0 (x∗ )en−1 + f 00 (x∗ )e2n−1 +O(e3n−1 ).
2
Furthermore we have

xn − xn−1 = (xn − x∗ ) − (xn−1 − x∗ ) = en − en−1 .

Subtracting x∗ from both sides of Eq. 1, and keeping in mind that by definition we have
f (x∗ ) = 0, gives then

(f 0 (x∗ )en + 12 f 00 (x∗ )e2n )(en − en−1 )


en+1 = en − ,
f 0 (x∗ )(en − en−1 ) + 21 f 00 (x∗ )(e2n + e2n−1 )

which can be rewritten using (e2n + e2n−1 ) = (en − en−1 )(en + en−1 ) as

f 0 (x∗ )en + 21 f 00 (x∗ )e2n


en+1 = en − ,
f 0 (x∗ ) + 21 f 00 (x∗ )(en + en−1 )
or
1 0 ∗ 0
f (x ) en en−1 f 00 (x∗ )
en+1 = 2
= en en−1 + O(e3 ).
f 0 (x∗ ) + 12 f 00 (x∗ )(en + en−1 ) 2f 0 (x∗ )
The relation
f 00 (x∗ )
en+1 = en en−1 (2)
2f 0 (x∗ )

1
is of the form
en+1 = ρn en
with
f 00 (x∗ )
ρn = en−1 ,
2f 0 (x∗ )
so if the method converges, i.e., limn→∞ en = 0, we have limn→∞ ρn = 0, so we have
established superlinear convergence, provided f 0 (x∗ ) 6= 0.
To establish the order of convergence let us postulate that

en+1 = Cn ern , (3)

where limn→∞ Cn = C, with C a constant and r > 1 is the rate of convergence to be


established. From Eq. 2 we know that
en+1
lim = C0 (4)
n→∞ en en−1

for some different constant C 0 . Using Eq. 3 we obtain for large n

en = Cern−1 ,

2
en+1 = Cern = C(Cern−1 )r = C r+1 ern−1 .
Substituting this in Eq. 4 gives
2
−r−1
lim C r ern−1
n→∞
= C 0.

Since we assume limn→∞ en = 0 this relation


√ can only be satisfied if r2 − r − 1 = 0, which
1+ 5
has the solution (satisfying r > 1) r = 2 .